A critical discourse analysis of racial violence in South Carolina, U.S.A.: implications for traveling while Black. Issue 19 (26th November 2019) - Duffy, Lauren N.; Pinckney, Harrison P.; Benjamin, Stefanie; Mowatt, Rasul
ABSTRACT: The purpose of this paper is to present a rich, detailed case that illustrates the way in which the discourse of racial violence has been constructed in the United States (U.S.), and how that has impacted Black travel. Using South Carolina, a state centrally-located along the East coast with historic, political, and social ties to the U.S. South as the context for this analysis, this paper employs a critical discourse analysis to examine the intersection of racial violence and tourism, situating cases of violence – historic to the modern. This study makes a case for more focused attention on the intersection of tourism and violence within the literature, as well as a call to the tourism industry to be proactive to discourses of violence, demonstrate a desire for diversity in their visitors, consider the critical issues of racial representation in their tourism products, and be aware of the emerging organizations supporting and facilitating Black travel.